Effects of the whole-body vibration direction on the cognitive response of standing subjects - Marelli, Stefano; Ferrario, Cristina; Lorenzini, Giuseppe; Ravi, Yuvan Sathya; Mazzoleni, Andrea; Marchetti, Enrico; Tarabini, Marco (Ergonomics, 2023)
This study aims to investigate the effect of whole-body vibration along different axes on the response time (RT) of standing subjects during a customised psychomotor vigilance task (PVT). Twenty-five subjects were exposed to harmonic vibration with amplitude of 0.7 m/s 2 RMS and frequencies between 1.5 Hz and 12.5 Hz. ANOVA was used to assess if the difference of RT with and without vibration had a statistical relevance. Results showed that the RT was statistically affected by the vibration only at frequencies below 2 Hz. The vibration at higher frequencies had a minor effect on the RT. The RTs during the vibration exposure was, on average, 15% higher than the RT post exposure. Practitioner summary: This study investigates the effects of whole-body vibration (WBV) along different axes on the response time (RT). We measured the RTs to a psychomotor vigilance task of 25 standing subject exposed to WBV. The cognitive response was statistically affected by the WBV and, on average RT have increased of 15%.